Intracellular target delivery of cell-penetrating peptide-conjugated dodecaborate for boron neutron capture therapy (BNCT). Issue 93 (16th October 2019) - Nakase, Ikuhiko; Katayama, Miku; Hattori, Yoshihide; Ishimura, Miki; Inaura, Shunsuke; Fujiwara, Daisuke; Takatani-Nakase, Tomoka; Fujii, Ikuo; Futaki, Shiroh; Kirihata, Mitsunori
Abstract : Boron neutron capture therapy (BNCT) technology using cell-penetrating peptides (CPPs) for enhanced cellular uptake of boron compounds and their controlled localization inside cells. Abstract : In this study, we designed and synthesized organelle-targeted cell-penetrating peptide (CPP)-conjugated boron compounds to increase their cellular uptake and to control the intracellular locations for the induction of sophisticated anticancer biological activity in boron neutron capture therapy (BNCT), leading to anticancer effects with ATP reduction and apoptosis when irradiated with neutrons in an in vitro BNCT assay.